Contextual Integration of Causal Coherence in People with Down Syndrome: Evidence from Figurative Comprehension (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Contextual integration is seldom explored in people with Down syndrome (DS). This study aimed to investigate this ability by comparing causal inferences made by people with DS who were presented with homonyms embedded within sentences and asked to choose which of three interpretations (figurative meaning, literal meaning, or unrelated meaning) was correct. Accuracy was the dependent variable. Each homonym was presented in a scenario familiar to the participants. The results revealed that the participants with DS were the least accurate in responding to figurative meanings and erred most compared to matched controls in chronological age and mental age. It was concluded that people with DS were developmentally delayed in causal inferences and weak central coherence is indeed a syndrome-general phenotype across populations with developmental disorders.